Penentuan Kriteria Evaluasi Kinerja Widyaiswara Menggunakan Nominal Group Technique - Rohmatulloh, R; Kusumastuti, Retno; Shiddiq, Julian Ambassadur (Department Industrial Engineering, University of Muhammadiyah Malang, 2016)
The role of competent trainers as an important part in creating an organizingÂ system of theÂ qualified training program. To improve the competencyof trainers to match the expected criteria, trainers evaluation of performance as the basic tools are needed. The purpose of this study is to determine the criteria or parameters that used in evaluating trainers performance. Determination of criteria is using the groupdecision-making techniques, namely nominal group technique (NGT).Â The NGT participants are trainer and planner. Successful criteria in consensus are established by the suitability of substance with the competence attended training, training participant satisfaction in classroom teaching ability, and the achievement of credit points. The criteria can be used as a reference for the evaluation and the results can be used for the appropriate competencies development that suitable with trainers requirement. The use of NGT is more effective to generate many ideas and determination of evaluation criteria.